1997
DOI: 10.1111/j.1365-2249.2006.03117.x
|View full text |Cite
|
Sign up to set email alerts
|

Insulin‐like growth factor‐binding protein‐2 in patients with prostate carcinoma and benign prostatic hyperplasia

Abstract: Several autoimmune diseases, mainly autoantibody-mediated, are attenuated by infusion of total IgG (IVIg). The efficacy varies widely from one patient to another. Using an experimental model of in vitro phagocytosis of autoanti-body-coated erythrocytes by mouse macrophages, we analysed the possible causes for such a variability. Our results indicated that the efficacy of the phagocytosis inhibition depends upon different factors, such as the isotype and the extent of polymerization of the immunoglobulin used f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(1 citation statement)
references
References 58 publications
1
0
0
Order By: Relevance
“…Interestingly, similar observations were made in a mouse model of haemolytic anaemia (Meite et al , 2000), suggesting that the LPS exacerbating effect may not be restricted to opsonized platelet destruction. In addition, in vitro assays showed that the suppressive effect of IVIg on the phagocytosis of opsonized red cells was greatly compromised when macrophages from virus‐infected mice were used (Leonard et al , 2006), a finding similar to the in vivo effects of LPS on IVIg efficacy reported in the present study. Additional work will be required to assess the potential impacts of these findings on the clinical management of ITP patients.…”
Section: Discussionsupporting
confidence: 86%
“…Interestingly, similar observations were made in a mouse model of haemolytic anaemia (Meite et al , 2000), suggesting that the LPS exacerbating effect may not be restricted to opsonized platelet destruction. In addition, in vitro assays showed that the suppressive effect of IVIg on the phagocytosis of opsonized red cells was greatly compromised when macrophages from virus‐infected mice were used (Leonard et al , 2006), a finding similar to the in vivo effects of LPS on IVIg efficacy reported in the present study. Additional work will be required to assess the potential impacts of these findings on the clinical management of ITP patients.…”
Section: Discussionsupporting
confidence: 86%